Kritik Hukum Pidana Islam Klasik: Metodologi Pembacaan Klasik Dengan Paradigma Konstitusional - Fanesti, Shabrian Hammam (Jurnal Restorasi Hukum, 2023)
Abstract: This article performs a reconstruction of classical Islamic penal law. The problem is a shift in the world's perspective on human values, including Indonesia. This shift began when the PBB established the Convention Against Torture and Other Crueal (CAT) and the International Covenant on Civil and Political Rights (ICCPR) as derivatives of the Declaration of Human Rights. It contains a commitment to abolish and reform criminal sanctions that are sadistic, degrading and killing people. This became an obstacle to the enforcement of classical Islamic penal code. Therefore, it is necessary to reconstruct the methodology of nash-nash readings of criminal law. This research is a qualitative research that is a literature review. The conclusion offered is that criminal law in Islam is a constitutional and dynamic affair so that the new Criminal Code (KUHP) is legally legal shari'i as a formulation of criminal law in Indonesia. Abstrak: Artikel ini melakukan rekonstruksi hukum pidana Islam klasik. Problematikanya adalah pergeseran cara pandang dunia terhadap nilai kemanusiaan, termasuk Indonesia . Pergeseran ini dimulai saat PBB menetapkan Convention Againts Torture and Other Crueal (CAT) dan International Covenant on Civil and Political Right (ICCPR) sebagai turunan dari Deklarasi Hak Asasi Manusia. Di dalamnya memuat komitmen untuk menghapus dan mereformasi sanksi pidana yang sadis, merendahkan mertabat manusia dan menghilangkan nyawa. Ini menjadi hambatan untuk penegakan hukum pidana Islam klasik. Oleh karena itu, perlu kiranya untuk merekonstruksi metodologi pembacaan nash-nash tentang hukum pidana. Penelitian ini merupakan penelitian kualitatif yang bersifat kajian pustaka. Kesimpulan yang ditawarkan adalah hukum pidana dalam Islam adalah urusan konstitusional dan dinamis sehingga Kitab Undang-undang Hukum Pidana (KUHP) baru legal secara syar’i sebagai rumusan hukum pidana di Indonesia.